The bias voltage and its influence on the etching rate of silicon - Fedorovich, О.А.; Hladkovskiy, V.V.; Polozov, B.P.; Kruglenko, М.P. (Вопросы атомной науки и техники, 2015)
The influence of the bias voltage on the silicon etching rate in the plasma-chemical reactor (PСR) with controlled magnetic fields have been investigated. The dependences of the silicon etching rate on the power, discharge current and on the pressure in the chamber PCR are obtained. It is found that at high bias voltages the main mechanism influencing on the etch rate drop is a material sputtering of the working electrode and its redeposition onto the surface of processed silicon wafers. Експериментально досліджено вплив напруги зміщення на швидкість травлення кремнію в плазмохімічному реакторі (ПХР) з керованими магнітними полями. З’ясовано, що при високих значеннях напруги зміщення основним механізмом, що впливає на зменшення швидкості травлення, є розпилення матеріалу робочого електрода і переосадження його на поверхню оброблюваних кремнієвих пластин. Экспериментально исследовано влияние напряжения смещения на скорость травления кремния в плазмохимическом реакторе (ПХР) с управляемыми магнитными полями. Установлено, что при высоких величинах напряжения смещения основным механизмом, влияющим на уменьшение скорости травления, является распыление материала рабочего электрода и переосаждение его на поверхность обрабатываемых кремниевых пластин.